Meltdown expected : crisis, disorder, and upheaval at the end of The 1970s - Leonard, Aaron J. (Rutgers University Press, 2024)
In January 1978, President Jimmy Carter proclaimed that "There is all across our land a growing sense of peace and a sense of common purpose." Yet in the ensuing months, a series of crises disturbed that fragile sense of peace, ultimately setting the stage for Reagan's decisive victory in 1980 and ushering in the final phase of the Cold War. Meltdown Expected tells the story of the power shifts from late 1978 through 1979 whose repercussions are still being felt. Iran's revolution led to a hostage crisis while neighbouring Afghanistan became the site of a proxy war between the USSR and the US, who supplied aid to Islamic mujahideen fighters that would later form the Taliban. Meanwhile, as tragedies like the Jonestown mass suicide and the assassination of Harvey Milk captured the nation's attention, the government quietly reasserted and expanded the FBI's intelligence powers. Drawing from recently declassified government documents and covering everything from Three Mile Island to the rise of punk rock, Aaron J. Leonard paints a vivid portrait of a tumultuous yet pivotal time in American history.